Pelatihan Penggunaan Software Ministep dalam Evaluasi Pembelajaran di SRISMI Al-Amin Kemaman, Terengganu, Malaysia: Training on Using Ministep Software in Learning Evaluation at SRISMI Al-Amin Kemaman, Terengganu, Malaysia - Vilmala, Berry Kurnia; Purwanto, Hadi; Sholihat, Neng; Minarti, Agus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Learning assessment is a crucial component of the educational process. Learning assessment can employ several software applications. By utilizing suitable software, educators may assess learning more effectively. Ministep is a software applicable in learning evaluation. This service aims to train instructors at SRISMI Al-Amin Kemaman Terengganu, Malaysia, in the utilization of the Ministep software for learning assessment. Lectures, demonstrations, and hands-on practice methods deliver this training. The training results indicated that before the instruction of SRISMI Al-Amin Kemaman educators in Terengganu, Malaysia, there was no awareness of the Ministep software. Upon completing the program, educators have adequate knowledge and skills to utilize the Ministep software for learning assessment. The conclusion is that this training is beneficial for teachers at SRISMI Al-Amin Kemaman, Terengganu, Malaysia, in utilizing the Ministep software for learning assessment.